Determination of PM2.5 and polycyclic aromatic hydrocarbons from incense burning emission at shrine for health risk assessment - Bootdee S. (2017)
© 2016 Turkish National Committee for Air Pollution Research and Control This study aims to determine fine particles (PM 2.5 ) and polycyclic aromatic hydrocarbons (PAHs) bounded with PM 2.5 emitted from incense burning at shrine to assess human health risk. The PM 2.5 samples were collected by a mini volume air sampler during special occasions and normal period at a shrine located in the city center of Chiang Mai, Thailand. The samples were analyzed for 16-PAHs by GC–MS. The descending order of 8- and 24-hrs PM 2.5 concentrations (μg/m 3 ) were 625 ± 147 and 406 ± 159 (Chinese New Year)  >  184 ± 85 and 133 ± 71 (other special occasions)  >  100 ± 35 and 50 ± 20 (normal period). Their concentrations in each occasion were significantly different due to number of visitors and amount of incense being burned. Total PAHs concentrations (ng/m 3 ) for 8- and 24-hrs in descending order were 90 ± 41 and 45 ± 29 (Chinese New Year), 71 ± 30 and 30 ± 12 (other special occasions) and 25 ± 15 and 14 ± 9 (normal periods). Correlation between PM 2.5 and total PAHs concentrations was relatively strong. In addition, PM 2.5 concentrations were highly correlated (r = 0.618) with carcinogenic PAHs (c-PAHs) indicated that carcinogenic compounds were dominant in particulate PAHs and generated from incense burning. The values of toxicity equivalent concentration (TEQ) indicate human health risk from PAHs inhalation. According to European guideline, it should be less than1 ng/m 3 in ambient air. During Chinese New Year, they were relatively high (32 ± 27 ng/m 3 (8 h) and 10 ± 4 ng/m3 (24 h)). Moreover, the isometric ratio analysis revealed that emission from incense burning was the main source of PM 2.5 and PM 2.5 -bound PAHs.